1990
DOI: 10.1007/bf00245259
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-deregulated mutants of Phanerochaete chrysosporium ?a lignin-degrading basidiomycete

Abstract: Two nitrogen-deregulated mutants of Phanerochaete chrysosporium, der8-2 and der8-5, were isolated by subjecting wild type conidia to gamma irradiation, plating on Poly-R medium containing high levels of nitrogen, and identifying colonies that are able to decolorize Poly-R. The mutants showed high levels of ligninolytic activity (14C-synthetic lignin----14CO2), and lignin peroxidase, manganese peroxidase and glucose oxidase activities in both low nitrogen (2.4 mM) and high nitrogen (24 mM) media. The wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…However, this sequence was not found in the published sequences of LIP genes. Our inability to find CRE-or AP-2-like sequences in the 5' regions of LIP genes is not entirely surprising since our previous data with the lip mutant (10) indicated that the product of a single genetic regulatory element controls the expression of the LIP gene family. Hence, it is possible that the CRE or AP-2 sequences, if involved in the regulation of expression of LIP gene family, might be located on a regulatory control locus defined by the lip mutation.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, this sequence was not found in the published sequences of LIP genes. Our inability to find CRE-or AP-2-like sequences in the 5' regions of LIP genes is not entirely surprising since our previous data with the lip mutant (10) indicated that the product of a single genetic regulatory element controls the expression of the LIP gene family. Hence, it is possible that the CRE or AP-2 sequences, if involved in the regulation of expression of LIP gene family, might be located on a regulatory control locus defined by the lip mutation.…”
Section: Discussionmentioning
confidence: 67%
“…Northern blot analyses were performed to determine whether cAMP inhibitors affect LIP and MNP production at the level of transcription. First, we used atropine as the cAMP inhibitor of choice because it is known to directly inhibit cAMP synthesis by inhibiting adenylate C inhibitor-treated and untreated cultures were fractionated by FPLC as described (10,11). The heme protein peaks were designated as in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, a decline in ligninolytic and cellulolytic enzyme activities has been observed in the forest floor [19]. Under laboratory conditions, high inorganic nitrogen concentrations can repress transcription of lignocellulolytic genes [53], [54]. This raises the question: might anthropogenic nitrogen deposition elicit a similar effect?…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we developed a potent cellulase mutant of Pleurotus florida, designated as PfCM4, induced by gamma radiation at a dose of LD 99 (0.51 kGy) (Sathesh-Prabu and Lee, 2012) that showed 17.24% more cellulolytic activity than wild type (p < 0.05). Boominathan et al, (1990) observed that gamma-ray radiation can change the genetic diversity of filamentous fungi and induce positive mutants. The genetic similarity of mycelia and basidiospores was altered according to the dose of gamma radiation (Lee and Chang, 1999).…”
Section: Introductionmentioning
confidence: 99%